A comparative research analysis of dried fruit husk performance on transmission and absorption behavior of sound - Villanueva, Abigail Joy C.; Juanga, Jean Marie V. (2014)
Durian and Coconut farming are the top agricultural industries in Davao City. However, these contribute to the 1.3 billion tons of organic waste produced in a year all over the world. Any object that is placed in a space can be a potential acoustical material. Yet, not all have the same function. Observing the shape and mass of the Durian and Coconut husk, these organic materials might be an efficient acoustical sound absorber or barrier. This research uses the Diffuse Field Sound Absorption model to get the reverberation time data and the Diffuse Field Sound Transmission model to get the sound transmission loss of each panel. The reverberation time data was used to compute the Noise Reduction Coefficient (NRC) while the sound transmission loss was used to compute the Sound transmission class (STC) of the panels. The results are the Durian Husk panel alone has an NRC of 0.22 and an STC of 29. The Coconut Husk panel has an NRC of 0.11 and an STC of 19. The NRC and STC results of the egg-crate and ¾? thick plywood were also taken for comparative purposes. It shows that the NRC of egg ?crate is 0.25 while its STC is 25. The ¾? thick plywood has an NRC of 0.13 and an STC of 13. It shows that if we compare the results, Durian Husk has the highest STC among all variables while its NRC is near to the NRC of egg- crate. Therefore, among the two organic panels, Durian Husk is the most efficient material to be processed further as a sound insulation. However, the panel alone is not an efficient sound acoustical insulation but by adding another material such as gypsum board or mineral fiber board it can fit to the required STC or NRC of a certain space. For classrooms, where sound barriers are necessary, the STC required is 50 while for offices the requirement is STC 45. By adding gypsum board to the durian husk panel we can obtain an STC of 55. This product can be used as a wall partition for offices. For classroom, we can double either the surface of durian husk or gypsum board to increase STC 55 to obtain the required STC wall partitions on this space. This process could be done on any material. Meanwhile, through adding mineral fiber board we can obtain an STC of 53 and this can be used for ceiling purposes of offices. However, this study should be furthered explored especially on the area of how to preserve the life span of the panel and how to increase its hour resistivity against fire.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2014